Cardamine hunanensis (Brassicaceae), a remarkable new species from Hunan (China) with fully bracteate racemes - Wu, Lie; Liu, W. J.; Mu, C.; Al-Shehbaz, Ihsan A. (Phytotaxa, 2021)
Cardamine hunanensis is described as a new Chinese-endemic species with fully bracteate racemes. Its differences from the closely related and bracteate-flowered C. lihengiana are discussed.